2014
DOI: 10.1080/13504851.2013.875103
|View full text |Cite
|
Sign up to set email alerts
|

Are per capita CO2emissions increasing among OECD countries? A test of trends and breaks

Abstract: We empirically analyze the trend characteristics of per capita CO 2 emissions in OECD countries from 1971 to 2009. We use a statistically robust procedure, which is valid regardless of whether per capita CO 2 emissions are trend stationary or contain a stochastic trend, to test for the presence of a deterministic trend and a structural break in the trend. Our results suggest that the trend in per capita CO 2 emissions shifts downward or is reversed for a number of OECD countries either after the 1970s oil shoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 6 publications
1
4
0
Order By: Relevance
“…In the same vein, differences in the usage of alternative energy sources are also linked to differences in fossil fuel endowment. It is therefore unsurprising that despite the existence of convergence evidence in carbon emissions (Emir et al ( 2019 ); Erdogan and Acaravci ( 2019 ); Erdogan and Solarin ( 2021 ); Payne and Apergis ( 2021 ); Solarin ( 2019 ); the outcome of this study is consistent with empirical findings of studies such as Aldy ( 2006 , 2007 ), Criado and Grether ( 2011 ), Herrerias ( 2013 ) Yamazaki et al ( 2014 ), and Li et al ( 2014 ) who have also provided evidence of divergence in carbon emissions.…”
Section: Discussion Of the Resultssupporting
confidence: 89%
“…In the same vein, differences in the usage of alternative energy sources are also linked to differences in fossil fuel endowment. It is therefore unsurprising that despite the existence of convergence evidence in carbon emissions (Emir et al ( 2019 ); Erdogan and Acaravci ( 2019 ); Erdogan and Solarin ( 2021 ); Payne and Apergis ( 2021 ); Solarin ( 2019 ); the outcome of this study is consistent with empirical findings of studies such as Aldy ( 2006 , 2007 ), Criado and Grether ( 2011 ), Herrerias ( 2013 ) Yamazaki et al ( 2014 ), and Li et al ( 2014 ) who have also provided evidence of divergence in carbon emissions.…”
Section: Discussion Of the Resultssupporting
confidence: 89%
“…Under these outcomes, Jaunky (2011) demonstrated that CO 2 emissions for highearning nations are I(1) integrated. Yamazaki et al (2014) indicated that in the OECD countries, per capita CO 2 emissions follow unit root. Barros et al (2016) applied fragmentary combination for the global series of carbon discharges and arrangement of every one of its five segments (gas, fluids, solids, concrete creation, and gas flaring).…”
Section: Literature Reviewmentioning
confidence: 99%
“…5. Research on the time series properties of CO 2 emissions in terms of the presence of unit root processes and the degree of persistence (see Heil and Selden, 1999;Lanne and Liski, 2004;Christidou et al, 2013;Yamazaki et al, 2014;Barros et al, 2016;Belbute and Pereira, 2017;Gil-Alana et al, 2017;Cai et al, 2018;and Gil-Alana and Trani, 2019) are relevant to understanding the behavior of CO 2 emissions over time; however, these studies do not explicitly examine the convergence of CO 2 emissions as defined by relative CO 2 emissions and stochastic convergence. Likewise, studies by List (1999), Lee and List (2004) 2017) with respect to the convergence of greenhouse gas emissions; the studies by Biligili and Ulucak (2018) and Ulucak and Apergis (2018) in regards the convergence of ecological footprint data; and the study by Bimonte (2009) who examines the convergence of protected areas in measuring environmental quality are also excluded from our review of the literature.…”
Section: Discussionmentioning
confidence: 99%